Teaching Media Used by EFL Pre-service Teachers in Pre-service Teaching Program - Triananda, Anak Agung Ayu Novi; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (Journal of Educational Study, 2023)
This study aimed to investigate the kinds of teaching media that were mostly used by EFL pre-service teachers (EFL PSTs), the reason underlying the use of certain kinds of teaching media, and the challenges encountered during the implementation of those particular kinds of teaching media in PLP Adaptif 2021 (PLP-A 21) teaching practicum. The subject of this research was 10 EFL PSTs from Ganesha University of Education majoring in English Language Education (ELE) who have executed in PLP-A 21. Furthermore, the researcher used a purposive sampling technique. The method used in data collection were observation, interviews, and document analysis. In this research, the data were collected using observation sheets, video recordings of teaching obtained from ELE PSTs, interview guidelines, and WhatsApp application, with a qualitative approach. The results showed that the kinds of teaching media mostly used by ELE PSTs in PLP-A 21 were multimedia, especially PowerPoint. The reason underlying the use of PowerPoint was because; it was easy to use, PowerPoint was a popular media for online education, it helped pre-service teachers easier convey the learning material, PowerPoint’s features helped them to design appealing media, and its use gave positive impacts on students' learning performance. Meanwhile, the challenges encountered by EFL PSTs during their implementation came from external factors, such as students do not have handphones, students' full handphone memory, and students' error handphones. Besides, there were also external factors, like EFL PSTs’ problem devices, e.g. PC got errors while implementing the media and EFL PSTs' unstable internet connection.